Soluble Colloidal Manganese Dioxide: Formation, Characterization and Application in Oxidative Kinetic Study of Ciprofloxacin - Gajala Tazwar; Vijay Devra (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Soluble colloidal manganese dioxide was formed by reduction of potassium permanganate with sodium thiosulphate in neutral aqueous medium at 25 ºC. The obtained nano-sized colloidal manganese dioxide was found to be dark reddish-brown in color and stable for several months. The formation of manganese dioxide was confirmed by UV-visible spectrophotometer and determination of oxidation state of Mn species in manganese dioxide. The effect of different concentration of sodium thiosulphate on the formation of manganese dioxide was also studied. The nano-sized colloid manganese dioxide was characterized by transmission electron microscopy and Fourier transform infrared spectrophotometer. The formed soluble colloidal manganese dioxide was used as an oxidant in oxidation of ciprofloxacin in perchloric acid medium at 35 ºC. The reaction was first-order concerning to concentration of manganese dioxide and hydrogen ion but fractional order with ciprofloxacin. The results suggest formation of complex between ciprofloxacin and manganese dioxide. The oxidation products were also identified based on stoichiometric and characterization results. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).